Critical Realism : Britain in the 1980s through the work of 28 Artists. - Edinburgh City Art Centre, Edinburgh; Stirling Smith Art Gallery, Stirling; Camden Arts Centre, Camden; Worcester Art Gallery, Worcester; Winchester Gallery, Winchester (Nottingham : Nottingham Castle Museum, 1987)
Bell, Steve ; Boyce, Sonia ; Biswas, Sutapa ; Brisley, Stuart ; Coe, Sue ; Cox, Phillip ; Crowley, Graham ; Currie, Ken ; Davies, Anthony ; Dwason, Joan ; Fairnington, Mark ; Graham, Paul ; Hewitt, John ; etc.
Critical Realism : Britain in the 1980s through the work of 28 Artists, A Nottingham Castle touring exhibition, 1987 : Nottingham Castle Museum, Nottingham, 29th August - 4th October 1987 ; Edinburgh Arts Centre, Edinburgh, 31st October - 5th December 1987 ; Stirling Smith Art Gallery, 19th December - 31st January 1988 ; Camden Arts Centre, Camden, 24th February - 20th March 1988 ; Worcester Art Gallery, Worcester, 2nd April - 15th May 1988 ; Winchester Gallery, Winchester, 24th May - 15th June 1988
boek
Keywords: Groot-Brittannië